A Review: Molecular Aberrations within Hippo Signaling in Bone and Soft-Tissue Sarcomas - Deel, Michael D.; Li, Jenny J.; Crose, Lisa E. S.; Linardic, Corinne M. (Frontiers in Oncology, 2015)
The Hippo signaling pathway is an evolutionarily conserved developmental network vital for the regulation of organ size, tissue homeostasis, repair and regeneration, and cell fate. The Hippo pathway has also been shown to have tumor suppressor properties. Hippo transduction involves a series of kinases and scaffolding proteins that are intricately connected to proteins in developmental cascades and in the tissue microenvironment. This network governs the downstream Hippo transcriptional coactivators YAP and TAZ, which bind to and activate the output of TEADs, as well as other transcription factors responsible for cellular proliferation, self-renewal, differentiation, and survival. Surprisingly, there are few oncogenic mutations within the core components of the Hippo pathway. Instead, dysregulated Hippo signaling is a versatile accomplice to commonly mutated cancer pathways. For example, YAP and TAZ can be activated by oncogenic signaling from other pathways, or serve as coactivators for classical oncogenes. Emerging evidence suggests that Hippo signaling couples cell density and cytoskeletal structural changes to morphogenic signals, and conveys a mesenchymal phenotype. While much of Hippo biology has been described in epithelial cell systems, it is clear that dysregulated Hippo signaling also contributes to malignancies of mesenchymal origin. This review will summarize the known molecular alterations within the Hippo pathway in sarcomas, and highlight how several pharmacologic compounds have shown activity in modulating Hippo components, providing proof-of-principle that Hippo signaling may be harnessed for therapeutic application in sarcomas.